PROPUESTA DE UN MODELO EXPERIMENTAL DE ENTERITIS AGUDA INDUCIDA POR INDOMETACINA EN RATAS ALBINAS - Ramos A., Dunia (2004)
Fifteen Holtzman male rats weighing 250 to 275 g were distributed in four groups. Group 1 was subcutaneously injected with 5% NaHCO3 (n=20). Groups 2, 3 and 4 received 15 mg/kg of indomethacin subcutaneously (n=10 rats/group). Macroscopic and microscopic evaluation of small intestine (jejunum-ileum) were carried out at first, second and third day after drug administration. Intestinal injury were observed along the mesenteric side of the middle and distal jejunum. Macroscopic lesions consisted of bowel thickening and dilatation, absence of the mucosa, hyperemia and multiple longitudinal and round ulcers. These lesions were observed at 24 h after drug injection and were present by 72 h. There were no statistical differences (p>0.05) between groups 2, 3 and 4, relating to gross lesions. Microscopically, lesions were characterized by erosion of the mucosa, fibrinous and bacterial infiltration, neutrophilic and lymphocytic infiltration, necrosis of the mucosa and the muscularis, bowel perforations and fibroblastic proliferation. Lymphocytes were present at first day (primary cellular indicator of inflammation) and neutrophils were present at second day (cellular indicator of persistence and severity). Microscopic lesions were most evident by 24 h after drug injection.